Business Mathematics text / Workbook - Gison- Salamat, Lorina; Regacho- Sevilla, Meryln ; Sta. Maria- Antonia Cruz (Mandaluyong City, 1998)
The topics in this textbook/workbook have been designed to achieve the objectives of equipping the students with the four fundamental operations such as addition, subtraction, multiplication and division, so as to build a firm foundation in the study of general principles and their applications in the field of Business and Cooperatives, Economics, Accounting, Office Administration, Computer Management, Statistics, Hotel and Restaurant Management, Marketing, Nutrition, Journalism, Tourism, Psychology and Food Technology
Keywords: Business Mathematics